An illustrated history of Britain - McDowall, David (Longman, 1997)
This book traces the development of the nation from prehistoric times to the present day. It looks at Britain history not merely in terms of kings, queens and battles, but also emphasises economic, social and intellectual forces and how these affected the everyday lives of people from different sections of society. The book is a history of Britain, not just of England. It looks at major development within Scotland, Wales and Ireland as well as their relations with England